Pseudoprogression in CAR-T cell therapy for solid tumor: Case report - Zhao, Xuan; Liu, Yanfen; Qin, Guohui; Ge, Yan; Li, Qinglong; Chen, Xinfeng; Tian, Ximei; Yu, Yong; Ren, Jiangtao; Zhang, Yi (Frontiers in Immunology, 2025)
We reported the pseudoprogression in an elderly patient with advanced gastric cancer after chimeric antigen receptor (CAR)-T cell therapy. The hepatic metastases enlarged 1 month after CAR-T cell infusion and then shrunk the next month as seen through computed tomography scanning. Based on a comprehensive evaluation that includes imaging, pathology, serum tumor markers, and clinical symptoms, we arrived at a diagnosis of pseudoprogression after CAR-T cell therapy, which has not been reported in previous studies. In this report, we provide detailed descriptions of the patient’s clinical presentation, imaging findings, treatment process, and follow-up outcomes. We believe that this case holds important implications for CAR-T cell therapy research and offers valuable insights for clinical practice.